Cultural Resilience in the Face of Crisis A Case Study of the COVID-19 Pandemic - Singh, Kapoor; Deepak, Anil; Asha, Pria (Journal Social Humanity Perspective, 2023)
The COVID-19 pandemic has had a significant impact on human cultures all across the world, presenting people with the challenge of responding to and adapting to unheard-of disasters. Cultural expressions have become crucial channels for people and communities to cope, connect, and find resilience during this time. This paper examines the subject of